2020
DOI: 10.3390/ijerph17155294
|View full text |Cite
|
Sign up to set email alerts
|

Are the Chinese Moving toward a Healthy Diet? Evidence from Macro Data from 1961 to 2017

Abstract: The change in diet structure is one of the critical features of social transformation, and diet structure is directly related to human health. In China, with rapid economic development, changes in the diet structure of the population have begun and are proceeding at a fairly rapid rate. In order to reveal how the Chinese diet is approaching or deviating from the nutritional goal, a novel index, NDBI (National Dietary Balance Index), is developed in this study to investigate the Chinese diet from 1961 to 2017 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Although protein is the raw material for muscle synthesis, Chinese people, particularly the older population, have higher carbohydrate intake and less protein intake. 42 Therefore, more attention should be given to the prevention and control of sarcopenia in older Chinese adults.…”
Section: Discussionmentioning
confidence: 99%
“…Although protein is the raw material for muscle synthesis, Chinese people, particularly the older population, have higher carbohydrate intake and less protein intake. 42 Therefore, more attention should be given to the prevention and control of sarcopenia in older Chinese adults.…”
Section: Discussionmentioning
confidence: 99%
“…In China, Diet Balance Index (DBI) was recommended to assess human diet quality. It can measure the dietary quality as a whole, and reflect not only insufficient dietary intake but also excessive dietary intake (22,23). DBI was established based on the Chinese dietary guidelines.…”
Section: Data Collection and Measuresmentioning
confidence: 99%
“…Han et al [ 20 ] evaluated the health score of Chinese diet based on dietary guidelines at the national level from 1961 to 2017. The authors found that, for Chinese diet, despite the severe deficiency has been significantly mitigated over the past 57 years, it is currently still lacking those high-quality and premium foods, such as dairy products.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the total caloric intake is investigated to indicate whether there is enough energy available for Chinese people in their food supply; fifteen common nutrients are examined to reveal whether Chinese people are nutrition secure. The studied period is from 1965 to 2018, during which China’s food system has experienced a great transition [ 20 , 23 ]. This study aims to provide policymakers information and implications to further improve the nutritional level of Chinese people.…”
Section: Introductionmentioning
confidence: 99%